Assessment of Staff Nurses' Knowledge, Attitudes, and Practices Regarding Infection Prevention and Control for Reducing Nosocomial Infections - Bibi, Husna; Iftikhar, Areej; Rimsha, .; Shahid, Savera; Mushtaq, Khudija; Saeeda, Khawer (Biological and Clinical Sciences Research Journal, 2025)
Nosocomial infections remain a major cause of morbidity, mortality, and prolonged hospital stay worldwide, particularly in low- and middle-income countries. Nurses play a pivotal role in infection prevention and control (IPC) due to their continuous patient contact. Assessing nurses' knowledge, attitudes, and practices (KAP) is essential for identifying gaps and strengthening infection control strategies in hospital settings. Objective: To assess the knowledge, attitudes, and practices of staff nurses regarding infection prevention and control measures aimed at reducing nosocomial infections at a tertiary care hospital in Lahore, Pakistan. Methods: A quantitative descriptive cross-sectional study was conducted among 385 registered staff nurses working in adult clinical departments of Sir Ganga Ram Hospital, Lahore, from February to June 2025. Participants were recruited using convenience sampling. Data were collected using a structured, self-administered questionnaire adapted from the World Health Organization hand hygiene assessment tool that covered socio-demographic characteristics, knowledge, attitudes, and practices related to IPC. Descriptive statistics were used to summarize KAP levels, while inferential analysis examined associations between demographic variables and KAP scores. Data were analyzed using SPSS version 25. Results: Among the 385 participants, 88.3% were female, and the majority were aged between 20 and 30 years. Overall, 91% of nurses demonstrated good knowledge of infection prevention, and 85% exhibited positive attitudes toward IPC. High awareness of the importance of hand hygiene before and after patient contact was observed (97.7%). However, notable knowledge gaps persisted, particularly regarding the correct use of alcohol-based hand rubs (46.8%). Despite favorable knowledge and attitudes, only 50.6% of nurses demonstrated good infection prevention practices, with lower compliance observed before patient contact and after glove removal. No statistically significant association was found between demographic variables and KAP scores (p > 0.05). Conclusion: Although staff nurses demonstrated strong knowledge and positive attitudes toward infection prevention and control, practical adherence to IPC measures was suboptimal. Targeted interventions focused on behavioral reinforcement, ongoing training, and improved institutional support are required to bridge the gap between knowledge and practice and reduce the burden of nosocomial infections.